Determinasi Kepatuhan Pajak Penjual E-Commerce Pasca Penerapan Pmk 37/2025 dan Coretax: Peran System Quality, Persepsi Risiko, dan Budaya sebagai Variabel Moderasi - Emi Lestari; Metta Julylia Wijaya; Jennyfer Faderica; Darwin Darwin; Philip Wijaya; Juy Celina Kwan (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The implementation of PMK 37/2025 and the Coretax system marks a significant transformation in digital tax administration in Indonesia, particularly for e-commerce sellers, who are now integrated into the tax collection process through digital platforms. This change makes tax compliance not only a regulatory obligation but also heavily influenced by how users perceive the quality of the system and the risks associated with it in their daily transactions. This study aims to analyze the influence of system quality and perceived risk on tax compliance, with trust as a mediating variable and uncertainty avoidance as a moderating variable. The method used is a quantitative approach through the distribution of questionnaires to e-commerce sellers who meet the criteria for taxpayers, with analysis using SEM-PLS. The results indicate that system quality and perceived risk have a positive and significant effect on trust and tax compliance. Furthermore, trust plays a significant role in strengthening compliance behavior, indicating that users tend to be more compliant when they have confidence in the system and tax authorities. However, uncertainty avoidance did not show a significant effect on tax compliance. These findings indicate that in the context of digital taxation, compliance is determined not only by regulatory enforcement but also by user perceptions, experience with the system, and the level of trust in the digital infrastructure used on an ongoing basis.